Nationalisation of motorcars in Lithuania After Soviet Occupation - Grigoraitis, Vidas (Genocidas ir rezistencija, 1999)
Over the past nine years, the press has published a few articles about the Soviet nationalisation of the real estate of Lithuanian higher education institutions, societies, estates and monasteries, as well as the movable property of the Lithuanian population, but it has not yet mentioned the rather important human property – the car. The nationalisation of passenger cars has not received much attention so far due to the narrowness and specificity of the topic. The aim of this article is to describe the situation of car transport in the last years before the war, to show the mechanism of the nationalisation of vehicles during the first Soviet occupation, from the adoption of the decisions to their implementation, to show which institutions and officials carried out the nationalisation and how the nationalised transport was distributed.